Psychosocial Work Factors, Work Stress And Musculoskeletal Discomfort In Computer Work In Malaysian Service Organizations - Zakerian, Seyed Abolfazl (2009)
This study represents a relatively comprehensive attempt to investigate the realationship between psychosocial work factors, work stress and musculoskeletal discomfort among office workers in service organizations who work with computers.